2001
DOI: 10.1097/00042737-200105000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inflammatory bowel disease on different dimensions of quality of life

Abstract: Quality of life is impaired in IBD. During relapse, clinicians should pay attention to digestive symptoms and psychological distress. In remission, they should be sensitive to systemic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
72
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 22 publications
13
72
3
3
Order By: Relevance
“…One of the major determinants of the extent to which quality of life is lowered by the diagnosis of IBD is disease activity (i.e., acute exacerbation vs. remission) [5, 56]. We were able to note an improvement in quality of life in individuals with relatively low disease activity, while there were no differences in clinical disease activity, assessed with the CAI, between the study groups at any time point.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…One of the major determinants of the extent to which quality of life is lowered by the diagnosis of IBD is disease activity (i.e., acute exacerbation vs. remission) [5, 56]. We were able to note an improvement in quality of life in individuals with relatively low disease activity, while there were no differences in clinical disease activity, assessed with the CAI, between the study groups at any time point.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, it is also conceivable that the effectiveness of mind/body therapy may be inversely related to disease activity. Casellas et al [56] showed that systemic symptoms (i.e., nonspecific symptoms such as fatigue, general discomfort, energy and appetite problems) and emotional dysfunction persist during periods of remission. The present results support these findings, and suggest that at least some of these symptoms may effectively be improved by mind-body therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), a chronic condition with fluctuating symptoms, an unpredictable course, and high rates of surgery, is thought to have similar negative repercussions [8][9][10][11][12][13][14][15] . Quality of life has been found to decline in parallel with increased disease severity 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Otros factores independientes reconocidos como el sexo femenino o el nivel educacional también existen (6). En cualquier caso, el factor más importante en la CVRS en la EII son los brotes de la enfermedad, afectando la CVRS del sujeto tanto en la percepción cualitativa como cuantitativa (7,8). No obstante, experiencias pasadas con la EII no influencian significativamente con la percepción de salud (9).…”
Section: Introductionunclassified